A study on diastolic dysfunction in asymptomatic type 2 diabetes mellitus with normal systolic function - Ilamaran, M.; Thangadhurai, A.; Kumar, P. Suresh; Nagalingam, Saranya (International Journal of Advances in Medicine, 2019)
Background: Diastolic heart failure, otherwise called as heart failure with preserved ejection fraction, is common finding of hypertensive heart disease, but various studies report a high incidence of diastolic heart failure in patients with type 2 diabetes mellitus in spite of the absence of coronary artery heart disease and hypertension. The objectives of the study were to determine the prevalence of dysfunction of left ventricle in diastole in type 2 diabetes mellitus patients and to compare with the non-diabetic individuals with that of asymptomatic type II diabetes patients. To assess the correlation of diastolic dysfunction in diabetes with age of patients, HbA1c levels, duration of diabetes, retinopathy, autonomic neuropathy. Methods: A prospective cross sectional among them 50 patients were diabetics and 50 were non-diabetic controls. Diastolic dysfunction was measured with standard echocardiographic parameters and the results were computed with corresponding variables of the patients. All the variables and their data were analysed for percentage, mean, standard deviation ‘t’ test and chi square test. The ‘t’-test was used to study the quantitative data while chi square test was used to study the qualitative data. Results: Among the study population 60% had diastolic dysfunction and 14% had diastolic dysfunction among cases and control group respectively. Diastolic dysfunction was present among 23.3% and the 76.7% of the age group groups of less than 45 and more than 45 years of age respectively. In this study poor glycaemic status was significantly associated with diastolic dysfunction, whereas duration of diabetes, retinopathy and autonomic neuropathy were not statistically significant. Conclusions: Present study reveals moderately high incidence of diastolic dysfunction in asymptomatic diabetic; subjects and, this finding was correlated with the HBA1C levels but not with retinopathy and autonomic neuropathy.